Práticas de gestão da qualidade aplicadas em micros, pequenas e médias empresas de confecção de Apucarana - Ferreira, Taylla Andressa Milan (2021)
Given the increased competition in recent years, companies have been looking for ways to obtain competitive commercial advantages. Among the existing alternatives, the use of quality practices and tools can provide such an event to these companies. Therefore, this work aims to analyze the use of quality management tools and practices in micro, small and medium-sized companies in the Apucarana clothing industry, highlighting the effectiveness of the use of the tools, the benefits of using them as well as the challenges found by the companies, and which tools are adopted by them, taking into account the profile of each one. To carry out such analysis, a data collection was carried out through a questionnaire sent to companies in the manufacturing sector in Apucarana. The study resulted in demonstrating that, regardless of the size of the company, they have sought to make their production process more standardized, through the use of quality management tools and/or practices that best suit the company's reality, with the greatest benefits pointed out better organization and cleaner environment, process improvement, material savings, loss reduction and increased productivity. But as changes generate barriers, it was expected that some would appear, so it is up to the company to face them in the best possible way.